LAPORAN KEUANGAN PEMERINTAH - Agung Darono (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2011)
Berger and Luckman (1990) defined contruction of reality as an angoing dynamic process that is (and must be) reproduced by people acting on their interpretations and their knowledge of it. In this view, the term of